Nghiên cứu ảnh hưởng của tỷ lệ các hợp phần đến phản ứng khâu mạch nhựa epoxy biến tính dầu ve bằng dianhydrit piromelitic - Thành, Đỗ Minh; Hiền, Lê Xuân; Việt Triều, Nguyễn Thị (Vietnam Journal of Chemistry, 2017)
The influence of the content of epoxy resin modified by castor oil (ECO), dianhydrite piromelitic (PMDA) and dimetylbenzylamin (DMBA) on the crosslinking reaction of ECO by PMDA have been studied and the optimal conditions for the curing have been determined. It was showed that at the optimal conditions: The mol ratio of anhydrite/epoxy = 1.3, reaction temperature 120 oC, the DMBA content of 2.3 % of the total mass of ECO and PMDA, the epoxy and anhydrite groups had been totally converted after 60 min of reaction. The mol ratio of anhydrite/epoxy = 1.3 have been determined to be optimal condition for formation of the cured coating having gel fraction, swelling degree, flexibility, adhesion, impact resistance and relative hardness of 93 %; 150 %; 1 mm, 1 point, 200 kG.cm, and 0.88, respectively. Keywords. Epoxy resin, castor oil, dianhydrite piromelitic, curing.